2023
DOI: 10.3390/ijms24065706
|View full text |Cite
|
Sign up to set email alerts
|

The Association of the Polymorphisms in the FUT8-Related Locus with the Plasma Glycosylation in Post-Traumatic Stress Disorder

Abstract: The molecular underpinnings of post-traumatic stress disorder (PTSD) are still unclear due to the complex interactions of genetic, psychological, and environmental factors. Glycosylation is a common post-translational modification of proteins, and different pathophysiological states, such as inflammation, autoimmune diseases, and mental disorders including PTSD, show altered N-glycome. Fucosyltransferase 8 (FUT8) is the enzyme that catalyzes the addition of core fucose on glycoproteins, and mutations in the FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…9 Mutations in the Fut8 gene in humans are closely associated with defects in core fucosylation and functional abnormalities. 10 Fut8 is a Golgi resident-inverting α-1,6 fucosyltransferase that transfers GDP-β- l -fucose to N -acetylglucosamine moieties adjacent to an asparagine (N) residue by a 1,6 linkage. 11 Studies in mouse models have shown that Fut8-null (Fut8 −/− ) mice exhibit severe growth retardation, early postnatal death, emphysema-like changes and abnormal development of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…9 Mutations in the Fut8 gene in humans are closely associated with defects in core fucosylation and functional abnormalities. 10 Fut8 is a Golgi resident-inverting α-1,6 fucosyltransferase that transfers GDP-β- l -fucose to N -acetylglucosamine moieties adjacent to an asparagine (N) residue by a 1,6 linkage. 11 Studies in mouse models have shown that Fut8-null (Fut8 −/− ) mice exhibit severe growth retardation, early postnatal death, emphysema-like changes and abnormal development of the immune system.…”
Section: Introductionmentioning
confidence: 99%